2010
DOI: 10.2135/cropsci2008.12.0712
|View full text |Cite
|
Sign up to set email alerts
|

Variability for Freezing Tolerance among 42 Ecotypes of Green‐Type Annual Bluegrass

Abstract: Limited information exists on the extent of genetic variability for freezing tolerance among perennial biotypes of annual bluegrass (Poa annua L.) that evolved under golf greens management. We characterized the freezing tolerance of 42 ecotypes collected across the United States and in Québec using plants hardened to low temperatures during fall and winter. We subsequently analyzed cold‐induced biochemical changes in a subset of ecotypes with varied levels of tolerance. There was a large variability among ecot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
4
31
0
Order By: Relevance
“…Although air temperature in the Antarctic falls well below ‫02מ‬ ЊC, soil temperature may be higher due to the insulation of snow cover. Nevertheless, seeds germinating from the soil samples indicate that Poa annua present at the site has developed high levels of freezing tolerance and confirm the findings of Dionne et al (2010). Following the worst scenario, Poa annua being a fertile species (Lush, 1988b) may dominate the soil seed bank and compete with two indigenous species of vascular plants in the Antarctic.…”
Section: Maciej Wó Dkiewicz Et Al / 417supporting
confidence: 60%
See 1 more Smart Citation
“…Although air temperature in the Antarctic falls well below ‫02מ‬ ЊC, soil temperature may be higher due to the insulation of snow cover. Nevertheless, seeds germinating from the soil samples indicate that Poa annua present at the site has developed high levels of freezing tolerance and confirm the findings of Dionne et al (2010). Following the worst scenario, Poa annua being a fertile species (Lush, 1988b) may dominate the soil seed bank and compete with two indigenous species of vascular plants in the Antarctic.…”
Section: Maciej Wó Dkiewicz Et Al / 417supporting
confidence: 60%
“…Poa annua has adapted to a broad range of weather conditions, from cold polar regions to hot deserts (Darmency and Gasquez, 1981;Frenot et al, 2001). The species has developed a different degree of freezing tolerance, even up to ‫72מ‬ ЊC (Dionne et al, 2010). Seeds can germinate over a wide range of environmental conditions (Vargas and Turgeon, 2004;Giełwanowska et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1), might play an important role in these processes, as suggested before (Volaire et al, 1998). A recent extensive screening of 42 annual bluegrass ecotypes, accumulating levan-type fructans, highlighted a strong correlation between the concentrations of high DP fructans and adaptation to subfreezing temperatures (Dionne et al, 2009). Noteworthy, the results also revealed that other known cryoprotectants, such as Suc and Pro, were not closely correlated with variations in cold tolerance in this species.…”
Section: Evolutionary Considerationsmentioning
confidence: 89%
“…Notably, the minimum temperatures reached in the reference mesocosms at the cold site were the least severe, and the highest AT % 15 N values were observed in these plots, whereas minimum soil temperatures of at least −4 • C were reached in the treatment plots at the cold site and in all of the warm site mesocosms, all of which featured relatively low 15 N values. Similarly, in other systems, grass ecotypes located at northern sites that are protected from cold air by thick snow cover have developed lower frost tolerance than conspecific ecotypes located in warmer locations that feature less snow cover, because the latter ecotypes experience more intense frost (Dionne et al, 2010).…”
Section: 05mentioning
confidence: 99%